2010
DOI: 10.1002/pd.2607
|View full text |Cite
|
Sign up to set email alerts
|

MR volumetry of the normal fetal kidney: reference values

Abstract: The present study provides reference data for normal fetal renal volumes, which may enable to identify fetuses at risk to develop congenital oligonephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
5
2
Order By: Relevance
“…MRI is generally considered the most reliable way to measure renal length and volume. In line with our findings, the largest study based on nuclear MRI so far, including 150 patients, did not find a significant difference in length or volume between the right and left kidneys [31]; another MRI study performed in 240 human fetuses without urogenital anomalies also did not show any difference in size between the right and left kidney [32].…”
Section: Discussionsupporting
confidence: 90%
“…MRI is generally considered the most reliable way to measure renal length and volume. In line with our findings, the largest study based on nuclear MRI so far, including 150 patients, did not find a significant difference in length or volume between the right and left kidneys [31]; another MRI study performed in 240 human fetuses without urogenital anomalies also did not show any difference in size between the right and left kidney [32].…”
Section: Discussionsupporting
confidence: 90%
“…However, the study of Bakker et al [23] showed that for reliable calculation of renal size in vitro, MRI with use of the voxel-count method is preferred. Compared to the study of Michielsen et al [2], where the MR-volumetry was performed in 240 fetuses, the range of the kidney volumes in the current study was slightly larger (Table 2). That study [2] however, included only healthy fetal kidneys, while our study involved also fetuses with CAKUT and pregnancies with earlier GA.…”
Section: Renal Imagingcontrasting
confidence: 85%
“…Compared to the study of Michielsen et al [2], where the MR-volumetry was performed in 240 fetuses, the range of the kidney volumes in the current study was slightly larger (Table 2). That study [2] however, included only healthy fetal kidneys, while our study involved also fetuses with CAKUT and pregnancies with earlier GA. In fetuses with CAKUT renal size is not an accurate reflect of the renal function (Beall et al 2007).…”
Section: Renal Imagingcontrasting
confidence: 85%
See 1 more Smart Citation
“…Four measurements determined from the mutant cohorts (Glis3‐null with vehicle and Glis3‐null with rapamycin) included: cyst volume; cyst volume percent of the entire kidney; TTP mean in tissue area; and TTP variance in tissue area. Structural changes (kidney volume, cyst volume and cyst percent) and a functional change (TTP mean) were fitted to a polynomial function of second order . TTP variance was fitted to a linear function.…”
Section: Methodsmentioning
confidence: 99%